High protein consumption in trained women: bad to the bone?. Issue 1 (31st January 2018) - Antonio, Jose; Ellerbroek, Anya; Evans, Cassandra; Silver, Tobin; Peacock, Corey A.
Abstract: Background: It has been posited that the consumption of extra protein (> 0.8 g/kg/d) may be deleterious to bone mineral content. However, there is no direct evidence to show that consuming a high-protein diet results in a demineralization of the skeleton. Thus, the primary endpoint of this randomized controlled trial was to determine if a high-protein diet affected various parameters of whole body and lumbar bone mineral content in exercise-trained women. Methods: Twenty-four women volunteered for this 6-month investigation ( n  = 12 control, n = 12 high-protein). The control group was instructed to consume their habitual diet; however, the high-protein group was instructed to consume ≥2.2 g of protein per kilogram body weight daily (g/kg/d). Body composition was assessed via dual-energy x-ray absorptiometry (DXA). Subjects were instructed to keep a food diary via the mobile app MyFitnessPal® . Exercise or activity level was not controlled. Subjects were asked to maintain their current levels of exercise. Results: During the 6-month treatment period, there was a significant difference in protein intake between the control and high-protein groups (mean±SD; control: 1.5±0.3, high-protein: 2.8±1.1 g/kg/d); however, there were no differences in the consumption total calories, carbohydrate or fat. Whole body bone mineral density did not change in the control (pre: 1.22±0.08, post: 1.22±0.09 g/cm 2 ) or high-protein group (pre: 1.25±0.11, post: 1.24±0.10 g/cm 2 ). Similarly, lumbar bone mineral density did not change in the control (pre: 1.08±0.16, post: 1.05±0.13 g/cm 2 ) or high-protein group (pre: 1.07±0.11, post: 1.08±0.12 g/cm 2 ). In addition, there were no changes in whole body or lumbar T-Scores in either group. Furthermore, there were no changes in fat mass or lean body mass. Conclusion: Despite an 87% higher protein intake (high-protein versus control), 6 months of a high-protein diet had no effect on whole body bone mineral density, lumbar bone mineral density, T-scores, lean body mass or fat mass.